Treatment rates for alcohol use disorders: a systematic review and meta‐analysis. (12th January 2021) - Mekonen, Tesfa; Chan, Gary C. K.; Connor, Jason; Hall, Wayne; Hides, Leanne; Leung, Janni
Abstract: Aims: To estimate the treatment rate for alcohol use disorders (AUDs) in the general adult population. Treatment rates were also considered in relation to economic differences. Methods: Systematic review and meta‐analysis. We searched PubMed, EMBASE, PsycINFO and CINAHL databases to identify studies that reported treatment rates for alcohol use disorders in the general population. Independent reviewers screened the articles based on predefined inclusion criteria. Data were extracted using a standardized data extraction form. We conducted quality assessments of the included studies. The overall treatment rates were estimated from studies that reported any treatment for AUDs from healthcare or informal non‐healthcare settings (any treatment). We estimated the separate treatment rates for each diagnostic category as reported in the primary studies: AUD as a single disorder, alcohol abuse and alcohol dependence. Data were pooled using a random‐effect model. Results: Thirty‐two articles were included to estimate the treatment rates (percentage treated among the total number of people with AUDs). The pooled estimate of people with AUDs who received any treatment were 14.3% (95% CI: 9.3–20.3%) for alcohol abuse, 16.5% (95% CI: 12–21.5%) for alcohol dependence and 17.3% (95% CI: 12.8–22.3%) for AUD. A subgroup analysis by World Bank economic classification of countries found that the treatment rate for AUD was 9.3% (95% CI: 4.0–15.7%) in low and lower‐middle‐income countries. Conclusion: Globally, approximately one in six people with AUDs receives treatment. Treatment rates for AUDs are generally low, with even lower rates in low and lower‐middle‐income countries.